Caesarean section audit spiral spanning 6 years of management in 3 major obstetric units of Glasgow. (18th April 2012) - Naz, A; Gibson, J; Hardwick, C; Moss, H
Abstract : Background: Caesarean section(CS) rates in Scotland have increased from 8.6% in 1976 to 25.4% in 2010.1 Aims & Objectives: In this study, we appraised the management of caesarean section against NICE and local guidelines, 2 with a view to target any areas of improvement. Specific objectives included a review of operative technique, type of anaesthetic and fetal distress parameters. Materials & Methods: Retrospective data collection of caesarean sections during a 2 week period. The audits were carried out in June 2005, November 2006 and January 2011. Results: All women received thromboprophylaxis. 95 % of CS were performed under regional anaesthetic. Umbilical cord pH performed in 75% of emergency CS. Decision to delivery times for the most urgent CS have reduced from a median of 33 (range 20-60) to 26 minutes (range 20-36 minutes)}, syntocinon use for third stage has increased from 91% to 98% and the rate of double-layer uterine closure has increased from 63% to 93%). Conclusion: There is evidence of improving care in this audit spiral as manifest from the results. However, compliance with guidelines is lower with regards to consultant involvement in decisions to perform emergency CS but this may reflect inadequate notekeeping rather than lack of communication with senior staff. The use of an operative proforma was shown in audit 2 of this spiral to be useful in improving surgical documentation.